2020
DOI: 10.33380/2305-2066-2020-9-4-53-58
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Process of Crushing in the Vibrocavitational Homogenizer

Abstract: Introduction. Vibration cavitation homogenizers are increasingly used in various industries, including the pharmaceutical industry – for the preparation of creams, gels to give them a homogeneous composition, and more recently for the extraction of valuable substances from plant materials. As we have shown earlier, a comparison of the extraction of dioscin from fenugreek seeds, carried out in devices of various designs, under the same conditions for organizing the process showed that the most effective method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thus, calendulaglycoside C ( 18) is associated with antitumor, anti-inflammatory, and antioedematous activities [47]. The derivatives of melilotigenin (15,19) were suggested to have anticancer activity [48]. Ilexoside XLVIII (24) exhibited inhibitory activity on acyl CoA cholesteryl acyl transferase [49].…”
Section: The Cross-validation Of the Quantitative Results Using The T...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, calendulaglycoside C ( 18) is associated with antitumor, anti-inflammatory, and antioedematous activities [47]. The derivatives of melilotigenin (15,19) were suggested to have anticancer activity [48]. Ilexoside XLVIII (24) exhibited inhibitory activity on acyl CoA cholesteryl acyl transferase [49].…”
Section: The Cross-validation Of the Quantitative Results Using The T...mentioning
confidence: 99%
“…When compressed again, these bubbles collapse, developing a pressure of up to hundreds of atmospheres, resulting in the formation of a highly intense shock wave. This leads to the additional mechanical destruction of solid plant particles and exudes small volumes of liquid from the phase interface, breaking up into small droplets and re-entering the plant [ 7 , 15 , 16 ]. This phenomenon helps to understand the high efficiency of NADES extraction using VAE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation technique with corporotomy provides high efficiency (90%) with an average penis shortening of about 5 mm [ 23 ]. The modified technique provides high efficiency (close to 100%) with insignificant (less than 1 cm) shortening of the penis, regardless of the bending angle, however, there is a slight decrease of the girth of the erect penis [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have revealed that tick-borne borreliosis pathogens are genetically heterogeneous and can be divided into two main groups. The first group comprises the causal agent of Lyme fever itself, and the second group includes causal agents of recurrent-type fevers [20]. The first group comprises the complex of Borrelia burgdorferi sensu lato (s.l.)…”
Section: Introductionmentioning
confidence: 99%